Syntaxin-1 N-peptide and H(abc)-domain perform distinct essential functions in synaptic vesicle fusion - Zhou, Peng (European Molecular Biology Organization, 2013)
Among SNARE proteins mediating synaptic vesicle fusion, syntaxin-1 uniquely includes an N-terminal peptide (‘N-peptide’) that binds to Munc18-1, and a large, conserved H(abc)-domain that also binds to Munc18-1. Previous in vitro studies suggested that the syntaxin-1 N-peptide is functionally important, whereas the syntaxin-1 H(abc)-domain is not, but limited information is available about the in vivo functions of these syntaxin-1 domains. Using rescue experiments in cultured syntaxin-deficient neurons, we now show that the N-peptide and the H(abc)-domain of syntaxin-1 perform distinct and independent roles in synaptic vesicle fusion. Specifically, we found that the N-peptide is essential for vesicle fusion as such, whereas the H(abc)-domain regulates this fusion, in part by forming the closed syntaxin-1 conformation. Moreover, we observed that deletion of the H(abc)-domain but not deletion of the N-peptide caused a loss of Munc18-1 which results in a decrease in the readily releasable pool of vesicles at a synapse, suggesting that Munc18 binding to the H(abc)-domain stabilizes Munc18-1. Thus, the N-terminal syntaxin-1 domains mediate different functions in synaptic vesicle fusion, probably via formation of distinct Munc18/SNARE-protein complexes.